2010
DOI: 10.1038/oby.2009.242
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based Weight Loss in Primary Care: A Randomized Controlled Trial

Abstract: Evidence is lacking regarding effective and sustainable weight loss approaches for use in the primary care setting. We conducted a 12-week randomized controlled trial to evaluate the short-term efficacy of a web-based weight loss intervention among 101 primary care patients with obesity and hypertension. Patients had access to a comprehensive website that used a moderate-intensity weight loss approach designed specifically for web-based implementation. Patients also participated in four (two in-person and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
280
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(290 citation statements)
references
References 30 publications
8
280
1
1
Order By: Relevance
“…We found that a greater proportion of women were interested in reading about other women's progress via their tweets (83 %) than were interested in tweeting about their own progress (71 %). Despite evidence that engagement is strongly related to outcomes [35][36][37][38][39][40], waning use is common in web-based behavioral interventions [41]. More frequent engagement in an online social network for weight loss is associated with better outcomes [22].…”
Section: Original Researchmentioning
confidence: 99%
“…We found that a greater proportion of women were interested in reading about other women's progress via their tweets (83 %) than were interested in tweeting about their own progress (71 %). Despite evidence that engagement is strongly related to outcomes [35][36][37][38][39][40], waning use is common in web-based behavioral interventions [41]. More frequent engagement in an online social network for weight loss is associated with better outcomes [22].…”
Section: Original Researchmentioning
confidence: 99%
“…The BFBW intervention was an evidence-based, moderate intensity, pragmatic intervention, 28,29 designed to produce weight loss through the modification of obesogenic lifestyle behaviors. Participants received tailored behavior change goals and tailored "prescriptions" for weight-related behavior changes signed by their provider.…”
Section: Methodsmentioning
confidence: 99%
“…It was challenging to accurately estimate the computer and IVR costs for the project, partially because the Webbased program was largely adapted from prior work; 28 and the fact that the IVR contract included costs for piloting, implementation, quality control, data transfer and overhead costs that did not vary by the number of users. We conservatively estimated that only the latter three categories would be needed for replication of the intervention, so the combined eHeath Technology cost (for both Web and IVR) was estimated at $32,499.…”
Section: Recruitment and Intervention Costsmentioning
confidence: 99%
“…There is a wealth of studies examining the effect of personalised programmes on weight loss (18)(19)(20)(21)(22)(23) as depicted in Table 2. Bennett et al conducted a 12-week randomised controlled trial among obese primary care patients with hypertension (n 101) (20) .…”
Section: Personalised Nutrition -How Effective Is It?mentioning
confidence: 99%